Peranan Komunikasi Organisasi Dalam Meningkatkan Kualitas Pelayanan Publik Di Era Otonomi Daerah - Revida, Erika (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2006)
In autonomy era, society needs the quality of public service in all sectors. Public service in the society’s right that must be fulfilled by government. Tp give the quality of public service needs an accurate and clear information from leader to subordinate, leader to leader, and subordinate to subordinate especially about the program and policy which have been formulated, so that every one in organization can understand what they need from others. It needs organizational communications. The channels of organizational communication are upward communication, downward communication, horizontal communication, and diagonal communication.